Pengembangan Pokdarwis dan SDM UMKM dalam Meningkatkan Efisiensi serta Efektivitas Bisnis - Sri Wahyuningsih; Catur Sasi Kirono; Fifi Hanafia; Nabila Nurfitria (CV. ITTC INDONESIA, 2026)
This community service program was designed to enhance the capacity of the Sukaragam Village community in adopting the Machida hydroponic system for melon cultivation as an innovative and sustainable agricultural practice. The community encountered several challenges, including limited understanding of hydroponic technology, inadequate technical skills in cultivation management, and insufficient knowledge of business management and agricultural marketing. The program was implemented through several stages, including needs assessment, educational outreach, technical training, hydroponic installation practice, mentoring, monitoring, and evaluation. The outcomes demonstrated improved participant knowledge and practical skills in assembling hydroponic systems, managing nutrient solutions, and cultivating melons using the Machida method. Furthermore, a hydroponic demonstration plot was established as a continuous learning facility and as the foundation for developing an independent community hydroponic farming group. This initiative is expected to improve agricultural productivity, create new entrepreneurial opportunities, and strengthen community economic resilience. In addition, the program supports the implementation of the Merdeka Belajar Kampus Merdeka (MBKM) policy through collaborative engagement between lecturers, students, and the local community.